Phương pháp xây dựng công cụ tra cứu và tìm kiếm nhanh các trang web trên internet/intranet - Anh, Ngô Trần (Journal of Computer Science and Cybernetics, 2016)
Various aspects of design for a fast seeking and searching utility for Web pages, especially which are written in Vietnamese, are discussed. A brief description of moludes in an implementation of such utility is also given